The dilemma in the management of haemodynamically stable pulmonary embolism with right heart thrombus. Issue 7 (23rd July 2019) - Rai, Manoj P; Herzallah, Khadar; Alratroot, Ahmad; Laird-Fick, Heather
Abstract : Right ventricular thrombus (RVT) can be life-threatening, since it has the potential to embolise and cause saddle pulmonary embolism (PE). We present a patient who initially presented with haemodynamically stable PE with evidence of RVT on echocardiogram. She was placed on heparin drip; however, she later developed cardiac arrest and died due to embolisation of RVT to the pulmonary vasculature. Although management of haemodynamically stable PE in patients with RVT is still a matter of debate, 1 given the outcome we suggest that thrombolysis or emergent embolectomy at the presentation, in this case, may have had a favourable outcome.